INGLIZ TILINI O‘QITISHDA KOMPETENSIYAVIY YONDASHUV ASOSIDA IJODIY VA INTELLEKTUAL SALOHIYATNI SHAKLLANTIRISH MODELI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This thesis analyzes the issues of forming students' creative and intellectual potential based on a competency-based approach to teaching English. The importance of the communicative approach in developing students' creative thinking, independent decision-making, and intellectual activity is highlighted.